Unveiling the Implicit: Arctic Coastal Aerosol Processes - Julia Schmale; Benjamin Heutte; Joanna Dyson (CHIMIA)
Arctic coasts cover more than 101,000 km and emulsify terrestrial, marine and socio-economic ecosystems. All three components produce specific emissions that contribute to the mix of atmospheric constituents, which are processed and dispersed in the coastal atmosphere to contribute to cloud formation through cloud condensation nuclei and ice nucleating particles. Clouds strongly influence the coastal energy balance. Importantly, Arctic coastal ecosystems are exposed to multiple pressures such as the warming atmosphere and ocean, the thawing cryosphere and the expanding anthropogenic activities. This means that coastal emissions and atmospheric processes are in constant evolution. Given the large area covered by coasts and the mix of emission sources, coastal aerosol processes deserve quantification to better understand their role in accelerated Arctic climate change.